2014
DOI: 10.1111/jnc.12935
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between orphan nuclear receptor Nurr1 expression and amyloid deposition in 5XFADmice, an animal model of Alzheimer's disease

Abstract: The functional roles of the orphan nuclear receptor, Nurr1, have been extensively studied and well established in the development and survival of midbrain dopamine neurons. Since Nurr1 and other NR4A members are widely expressed in the brain in overlapping and distinct manners, it has been an open question whether Nurr1 has important function(s) in other brain areas. Recent studies suggest that up-regulation of Nurr1 expression is critical for cognitive functions and/or long-term memory in forebrain areas incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 30 publications
3
48
0
Order By: Relevance
“…In the present study, Nurr1 immunoreactivity was primarily observed in pyramidal neurons and granule cells, which are well established as principal neurons of the hippocampus ( 28 ), in young, adult and aged gerbil hippocampi. The results of Nurr1 immunoreactivity in the hippocampi were generally consistent with those of a previous study in C57BL/6 mice, which demonstrated that clear and specific Nurr1 immunoreactivity occurred in the hippocampus ( 29 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, Nurr1 immunoreactivity was primarily observed in pyramidal neurons and granule cells, which are well established as principal neurons of the hippocampus ( 28 ), in young, adult and aged gerbil hippocampi. The results of Nurr1 immunoreactivity in the hippocampi were generally consistent with those of a previous study in C57BL/6 mice, which demonstrated that clear and specific Nurr1 immunoreactivity occurred in the hippocampus ( 29 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is expressed in several brain areas and plays important roles in various neural processes including cognitive functions and/or long-term memory in forebrain areas and hippocampal formation. Immune-fluorescence staining with a specific NR4A2 antibody in 5XFAD mice showed that the NR4A2 protein was prominently localized in brain areas with Aβ plaque accumulation, highlighting a possible involvement of this protein in AD pathology 60 . The potential regulation of NR4A2 by miR-184 requires further functional testing but leads us to suggest that the loss of expression of miR-184 in LOAD hippocampus may contribute to NR4A2 accumulation in Aβ plaques.…”
Section: Discussionmentioning
confidence: 96%
“…A reduction in Nurr1 levels has been reported in several neurodegenerative diseases [18]. The importance of Nurr1 in PD pathology is well established [19], and reduced Nurr1 levels have been reported in AD animal models and the brains of patients with AD [112,113]. Therefore, Nurr1 has been suggested as a valid biomarker for neurodegenerative diseases and a therapeutic target [18,23].…”
Section: Discussionmentioning
confidence: 99%